Is Aristotle’s Response to the Argument for Fatalism in De Interpretatione 9 Successful? (2014)
The goal of this paper is to figure out whether Aristotle’s response to the argument for fatalism in De Interpretatione 9 is a success. By “response” it is meant not simply the reasons Aristotle offers to highlight why fatalism does not accord with how we conduct our lives, but also the solution he devises to block he argument for fatalism. This paper finds that a) Aristotle’s argument for fatalism is essentially bivalence plus that the truth of a proposition implies necessity, b) that Aristotle’s solution is to restrict bivalence, c) that this solution is coherent, and d) that while this solution does not rule out the possibility of fatalism, it does succeed in blocking the argument for fatalism offered within chapter 9.